2016
DOI: 10.1515/abcsb-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment of Fulvic Acid Plays a Stimulant Role in Protection of Soybean (Glycine max L.) Leaves Against Heat and Salt Stress

Abstract: The purpose of this study was to illuminate the effects of fulvic acid in plants’ stress signaling pathway. 2.0 mg/l fulvic acid was sprayed on soybean leaves for 3 days at 12 h intervals, followed by treatment of 150 mM NaCl or exposed to heat stress at 35°C for 2 h over 2 days. Pre-treatment with fulvic acid increased the relative water content (RWC), antioxidant enzyme, isoenzyme activities (SOD, APX, GST), as well as alleviated the stress-induced oxidative damage by decreasing the levels of hydrogen peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Many studies have shown that FA has many plant physiological activities. FA could significantly alleviate the toxic symptoms of Cd on lettuce seedlings [15].. And FA could protect soybean and barley against salt stress [16,17]. Moreover, FA played important roles in the improvement of drought resistance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that FA has many plant physiological activities. FA could significantly alleviate the toxic symptoms of Cd on lettuce seedlings [15].. And FA could protect soybean and barley against salt stress [16,17]. Moreover, FA played important roles in the improvement of drought resistance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 1 up-regulated cytochrome C oxidase (c119073.graph_c0) was discovered in this study, which is found in the electron transport system of mitochondria and generates two molecules of water by transferring electrons to O 2− . Because mitochondria, but not chloroplasts, create ROS, defects or shortages in this enzyme can be lethal to plants [ 74 , 75 ]. This finding shows that shielding mitochondria from oxidative damage produced by heat stress can aid in heat stress management.…”
Section: Discussionmentioning
confidence: 99%
“…There are no previous reports about the effect of FA on HSP70 gene expression in animals. However, FA administration can downregulate the mRNA HSP70 expression in plants under saline stress conditions (Dinler, Gunduzer, & Tekinay, ). We can interpret that dietary FA did not cause stress in shrimp and might contribute to the reduction in stress in shrimp under intensive culture conditions, which merits further investigation.…”
Section: Discussionmentioning
confidence: 99%